The Relationship Between Mental Health and Maternal Functioning in Postpartum Women - Riska Amalia, Nur Alifka; Andi Irhamniah Sakinah,; Azizah Nurdin,; Arlina Wiyata Gama,; Mukhlis Mukhtar, (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
The prevalence of mental health related to anxiety, depression, and postpartum stress in Asia is high and varies widely, between 26-85%, while in Indonesia it is between 50-70% in postpartum mothers. Maternal functioning is a multidimensional concept that includes personal care, babies, families, social activities and work. Objective: to determine the relationship between mental health and maternal functioning in postpartum mothers. This research uses an observational analytic method with a cross-sectional approach. The sample used was postpartum mothers who met the criteria with a total sample of 100 samples. The data collected in this study used secondary data from medical records and primary data through questionnaires, then analyzed using the Chi-Square test. The results of this study indicate that there is a significant relationship between anxiety and maternal functioning while for depression and stress there is no significant relationship with maternal functioning in postpartum mothers